Database and Applications Security: Integrating Information Security and Data Management - Thuraisingham, Bhavani (CRC Press, 2009)
As the demand for data management increases, so does the need for maintaining security of databases, applications, and information systems. The advent of the Web increased the likelihood of unauthorized access and malicious corruption, bringing to the forefront the necessity for effective mechanisms that secure critical information.